2015
DOI: 10.1007/s10858-015-9900-4
|View full text |Cite
|
Sign up to set email alerts
|

Complete dissociation of the HIV-1 gp41 ectodomain and membrane proximal regions upon phospholipid binding

Abstract: The envelope glycoprotein gp41 mediates the process of membrane fusion that enables entry of the HIV-1 virus into the host cell. Strong lipid affinity of the ectodomain suggests that its heptad repeat regions play an active role in destabilizing membranes by directly binding to the lipid bilayers and thereby lowering the free-energy barrier for membrane fusion. In such a model, immediately following the shedding of gp120, the N-heptad and C-heptad helices dissociate and melt into the host cell and viral membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 61 publications
2
28
1
Order By: Relevance
“…Roche et al [21], who used a truncated gp41 ectodomain construct where the immunodominant loop (IL) was replaced by a flexible linker, found that the protein was monomeric in the detergent dodecyl phosphocholine (DPC). The same behavior was observed also in the presence of the membrane proximal external region (MPER) [22].…”
supporting
confidence: 68%
“…Roche et al [21], who used a truncated gp41 ectodomain construct where the immunodominant loop (IL) was replaced by a flexible linker, found that the protein was monomeric in the detergent dodecyl phosphocholine (DPC). The same behavior was observed also in the presence of the membrane proximal external region (MPER) [22].…”
supporting
confidence: 68%
“…After isolating the insoluble fraction, the constructs were fractionated on size-exclusion Superdex-200 or -75 columns (GE Healthcare, Piscataway, NJ) under denaturing conditions followed by reverse-phase high-performance liquid chromatography as described previously. 49 6-helix, 5-helix, core S , and core SP were folded by dialysis against 50 mM sodium formate (pH 3) followed by buffer exchange with 10 mM Tris-HCl (pH 7.6) and 150 mM NaCl (buffer A), concentrated to ~ 2 mg/mL, and stored.…”
Section: Methodsmentioning
confidence: 99%
“…Ground-breaking developments – involving diverse technologies including single molecule fluorescence resonance energy transfer (smFRET) [10], cryo-electron microscopy (cryo-EM) [11••,12••], X-ray crystallography [13••,14••] and nuclear magnetic resonance (NMR) [15,16] – are revealing the structures and conformations of the HIV-1 Env, a type 1 fusion machine that uses conformational change to drive fusion of viral and cellular membranes. These studies provide the context in which to situate bNAb sites of vulnerability.…”
Section: Introductionmentioning
confidence: 99%